2004
DOI: 10.1002/mame.200300262
|View full text |Cite
|
Sign up to set email alerts
|

Crack Patterns in Thin Polymer Layers

Abstract: Summary: During the solidification of thin polymer layers different crack patterns can occur. There are several mechanisms of the development of regular crack defects and layer fractures. In case of self‐organization caused by Marangoni instability at the fluid layer surface the substrate can be periodically uncovered by spreading motions when dewetting hinders a back flow from the higher spots of the layer. Another type of crack patterns is generated from shrinkage processes and stress differences in the dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Applications of micro-scaled relieves obtained under evaporation of polymer solutions as biomedical interfaces has been discussed intensively as well [4,5]. It was demonstrated that under particular conditions, intensive evaporation of the solution gives rise to ordered self-assembled patterns on a length scale significantly exceeding molecular dimensions [6][7][8][9][10][11][12][13][14]. Similar patterns were observed under evaporation of volatile liquids [15,16].…”
Section: Introductionmentioning
confidence: 92%
“…Applications of micro-scaled relieves obtained under evaporation of polymer solutions as biomedical interfaces has been discussed intensively as well [4,5]. It was demonstrated that under particular conditions, intensive evaporation of the solution gives rise to ordered self-assembled patterns on a length scale significantly exceeding molecular dimensions [6][7][8][9][10][11][12][13][14]. Similar patterns were observed under evaporation of volatile liquids [15,16].…”
Section: Introductionmentioning
confidence: 92%
“…Weh and theoretically treated by De Gennes [2,15] . It seems that these structures have a potential as photonic molecules.…”
Section: Optical and Sem Microscopy Study Of The Structure Of Self-asmentioning
confidence: 99%
“…3) or centers (see Fig. 6) could be explained in the framework of the concept developed by Weh, who related the effect to the Marangoni instability, which induced spreading motions of the solution [2] . However, insensitivity of the mesoscopic cell size to the kind of polymer or used solvent calls for an explanation, which will be proposed below.…”
Section: Influence Of the Parameters Of The Dip-coating Process On Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of this pattern is not clear, and is related by many researchers to various kinds of interfacial instabilities: Marangoni (surface-tension-driven), evaporation or masstransport-driven ones. [23][24][25][33][34][35][36][37][38][39][40][41][42] The high dispersion of pore sizes seen in Figure 2 makes this pattern unsuitable for most of the applications mentioned above.…”
Section: Makeup Of Micro-porous Pei Filmsmentioning
confidence: 99%